Scientific explanation: A study of the function of theory, probability and law in science - Braithwaite, Ricard bevan (New York Harper & Brothers, 1960)
Each science proceeds by inventing general principles from which are deduced the consequences to be tested by observation and experiment; the author shows how the implications of this process explain some of its more baffling features and resolves many of the difficulties that philosophers have found in them.
Keywords: Science methodology; sciences philosophy; Scientific explanation